SENSOR NETWORK FOR ENVIRONMENT MONITORING - BORDIAN, DMITRY; TURCAN, ANA; ABABII, CONSTANTIN; LASCO, VICTOR; FRATAVCHAN, VALERIY (Чернівці: Черн. нац. ун-т, 2022)
This paper presents the results of the development of a sensor network for environment monitoring. The system presents a mesh of data processing nodes distributed in the monitoring space that perform the operations of acquisition, storage, processing and communication between neighboring nodes. Mathematical models are developed to perform the interpolation operation.
Keywords: Sensor Network, Grid Computing, Environment Monitoring, Distributed Computing, Interpolation.